A new Peruvian species and new records of the genus Piestus Gravenhorst (Coleoptera: Staphylinidae) - Pérez, Luis; Rodríguez, Maryzender; Asenjo, Angélico (Zootaxa, 2017)
A new species of the genus Piestus Gravenhorst is described from Peru, P. chullachaqui sp. nov. (Cuzco). Photographs and drawings of the major diagnostic characters are provided. A key to Piestus species is modified to include the new species. New records are provided for Piestus angularis Fauvel, Piestus bicornis (Olivier), Piestus fronticornis (Dalman), Piestus lacordairei Laporte, Piestus longipennis (Fauvel), Piestus mexicanus Laporte, Piestus minutus Erichson, Piestus pennicornis Fauvel, Piestus spinosus (Fabricius), Piestus sulcatus Gravenhorst, Piestus surrufus Caron et al. and Piestus validus Sharp. Cladistic analysis is made to know the relationship of the P. chullachaqui sp. nov. within Piestus.